Evaluating the relationship between noise reduction and object thickness in scatter correction processing - Tsuchiya, Hiroki; Takaki, Takeshi; Ota, Satoru; Fujita, Yuki; Murakami, Seiichi (Radiation protection dosimetry, 2025)
Physical grids (PGs) are used in portable bedside radiography to reduce scattered X-rays that reach the detector. Because the use of PGs degrades image quality due to oblique incidence of X-rays or deviation of the center line on the grid, scatter correction (SC) processing is often used instead of PGs. This study aimed to evaluate the relationship between object thickness and noise reduction in SC processing. Polymethyl methacrylate (PMMA) phantoms of different thicknesses (16, 20, 26, and 30 cm) were used as objects. The Burger phantom was placed at the center of the thickness direction of the PMMA phantoms. Images were acquired with PGs, without PGs, and with SC processing which consists of contrast improvement processing and noise reduction processing. Contrast and noise were evaluated. Contrast of images without PG improved when SC processing was used. However, the effect of noise reduction process decreased with increase in the thickness of PMMA, and significant decrease was observed when the thickness of PMMA was ≥26 cm. In SC processing, the effect of noise reduction decreased with the increase in object thickness. These findings suggest that the applicability of SC processing may be limited, particularly in large patients.